Laparoendoscopic single‐site simple nephrectomy and reduced port procedure for inflammatory nonfunctioning kidney. Issue 3 (17th March 2021) - Kaneko, Go; Hattori, Seiya; Shirotake, Suguru; Kanao, Kent; Hara, Satoshi; Oyama, Masafumi
Abstract : Introduction: To describe laparoendoscopic single‐site simple nephrectomy and reduced port simple nephrectomy for inflammatory nonfunctioning kidney. Case presentation: Case 1: a 58‐year‐old female with fever was referred to our hospital. Computed tomography demonstrated a markedly atrophic right kidney and mild hydronephrosis. Case 2: a 64‐year‐old male with a history of several intra‐abdominal surgeries visited our hospital with a complaint of left back pain and fever. Computed tomography demonstrated left marked hydronephrosis, thinning of renal parenchyma, and duplicated inferior vena cava. After antibiotic treatment, transperitoneal reduced port simple nephrectomy and retroperitoneal laparoendoscopic single‐site simple nephrectomy were performed in Case 1 and 2, respectively, because the function of the affected kidney was almost lost on renography. Although adhesion was slightly noted around the renal hilum in Case 1, neither conversion to laparotomy nor placement of additional ports was needed. Conclusion: Laparoendoscopic single‐site simple nephrectomy and reduced port simple nephrectomy for inflammatory nonfunctioning kidney may be options for experienced laparoscopic surgeons.